PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS TERHADAP PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015) - Rio Muhammad Ariono; Hj. Maslicha Hj. Maslicha; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2017)
The purpose of this research is 1). to know the influence of corporate social responsibility toward company value, 2). to know the effect of profitability to company value, 3). to know the influence of corporate social responsibility interaction with profitability to company value.The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2013-2015. Sample selection using purposive sampling. Based on the criteria, obtained 50 companies that became the sample in this study. The method used in this study using multiple linear regression method.Based on the results of the analysis can be put forward several conclusions as follows: 1). T test results show that for Social Responsibility variable has no significant effect on firm value, but profitability has positive significant effect on firm value and interaction between CSR and profitability (ROA) Significant to company value. 2). The result of f test shows that CSR, profitability (ROA) and interaction between CSR and profitability (ROA) simultaneously have significant influence to firm value.